Ciri-ciri Wahhabi Menurut Pandangan Muḥammad Abu Zahrah dalam Tarikḥ al-Madhahib al-Islamiyyah - Rushda Amirah Ishak; Wan Mohd Fazrul Azdi Wan Razali (USIM Press, 2024)
Vol. 5 No. 1 (2020): Jurnal Sains Insani